The Ins and Outs of Water in Olivine-Hosted Melt Inclusions: Hygrometer vs. Speedometer - Barth, Anna; Plank, Terry (Frontiers in Earth Science, 2021)
The amount of water dissolved in magmas at depth beneath volcanoes is fundamental to a wide range of magmatic and eruptive processes due to water’s dominant control on magma generation, viscosity, and buoyancy. Since magmas degas most of their initial water content upon ascent and eruption, the primary record of magmatic water evolution exists within melt inclusions trapped inside crystals, especially olivine. However, the discovery of rapid H+ diffusion through olivine has called into question the fidelity of the melt inclusion water record. How compromised is the vast existing and growing dataset of melt inclusion water contents? What are the circumstances favorable for recording primary or pre-eruptive water concentration? Even if inclusions are compromised, diffusive water loss can be exploited to constrain magma decompression rates, a critical parameter that affects conduit processes. Here, we outline the current understanding of factors controlling water loss: the olivine/melt partition coefficient, the diffusive transport of water through olivine, the distance between inclusion and crystal rim, the melt inclusion size, and the exterior magma’s water evolution. We combine these parameters into a regime diagram that can be used to guide when melt inclusions may be used as hygrometers and when they are better suited to act as magma speedometers. We develop diagnostic tools to recognize where and when water loss has occurred in a magma’s ascent history, and we outline quantitative tools that may be used to restore the primary and/or pre-eruptive water content. The intent of this paper is to guide researchers in the interpretation of existing melt inclusion data, and to aid in the design of new studies that maximize the valuable information melt inclusions may convey on the evolution of water in magmas prior to eruption.